2013
DOI: 10.1371/journal.pone.0082351
|View full text |Cite
|
Sign up to set email alerts
|

Optic Nerve Head Blood Flow Autoregulation during Changes in Arterial Blood Pressure in Healthy Young Subjects

Abstract: AimIn the present study the response of optic nerve head blood flow to an increase in ocular perfusion pressure during isometric exercise was studied. Based on our previous studies we hypothesized that subjects with an abnormal blood flow response, defined as a decrease in blood flow of more than 10% during or after isometric exercise, could be identified.MethodsA total of 40 healthy subjects were included in this study. Three periods of isometric exercise were scheduled, each consisting of 2 minutes of handgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Autoregulation was also found in the ONH, as evidenced by a 30% increase in OPP, but there was no corresponding increase in ONH blood flow (measured by LDF) after three sessions of 2-min handgripping (Boltz et al 2013c). Boltz et al (2013a) demonstrated that 6 min of squatting increased OPP by 84% and the ONH red cell flux (measured by LDF) by 27%.…”
Section: Isometric Exercise and Ocular Perfusionmentioning
confidence: 92%
“…Autoregulation was also found in the ONH, as evidenced by a 30% increase in OPP, but there was no corresponding increase in ONH blood flow (measured by LDF) after three sessions of 2-min handgripping (Boltz et al 2013c). Boltz et al (2013a) demonstrated that 6 min of squatting increased OPP by 84% and the ONH red cell flux (measured by LDF) by 27%.…”
Section: Isometric Exercise and Ocular Perfusionmentioning
confidence: 92%
“…Sample size calculation was performed according to previous reproducibility data in healthy subjects (Boltz et al. ). The standard variation for ONHBF is approximately 15%.…”
Section: Methodsmentioning
confidence: 99%
“…The protocol followed the schedule we have previously used in healthy subjects (Boltz et al. ). Dilatation of the pupil of the right eye was obtained with topical tropicamide (Mydriaticum Agepha‐Augentropfen, Vienna, Austria).…”
Section: Methodsmentioning
confidence: 99%
“…33,138 The mechanisms of autoregulation in the human eye are, however, complex and not fully explored. [139][140][141][142][143][144][145][146][147][148] No strategy is currently available to normalize autoregulation in disease states associated with abnormal blood flow regulation in response to changes in perfusion pressure. In addition, the time course of loss of RGCs and decline in blood flow is not fully established.…”
Section: Other Approachesmentioning
confidence: 99%